2021
DOI: 10.1021/acsami.1c15346
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of Thermal Transport in Graphene Composites: Effect of Lateral Dimensions of Graphene Fillers

Abstract: We report on the investigation of thermal transport in noncured silicone composites with graphene fillers of different lateral dimensions. Graphene fillers are comprised of few-layer graphene flakes with lateral sizes in the range from 400 to 1200 nm and the number of atomic planes from 1 to ∼100. The distribution of the lateral dimensions and thicknesses of graphene fillers has been determined via atomic force microscopy statistics. It was found that in the examined range of the lateral dimensions, the therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 97 publications
0
28
0
Order By: Relevance
“…Due to the weaker sepiolite network, GNPs of H-25 might tend to "wrinkle" more, leading to internal strains and effective particle length reduction and thus potentially reducing their thermal conduction capability. 36 Larger lateral size GNPs dictate higher intrinsic TC, as supported by theoretical calculations, simulations, and experimental evidence: 18,37 it was suggested that with increasing lateral size of graphene, a higher amount of lowfrequency acoustic phonons is excitable, thus enhancing its intrinsic TC. 17,18 However, the highest TC enhancement and TC efficiency were measured for GNPs with the smaller MLD (H-15 GNP) for both base fluids (Figure 5).…”
Section: Resultsmentioning
confidence: 88%
“…Due to the weaker sepiolite network, GNPs of H-25 might tend to "wrinkle" more, leading to internal strains and effective particle length reduction and thus potentially reducing their thermal conduction capability. 36 Larger lateral size GNPs dictate higher intrinsic TC, as supported by theoretical calculations, simulations, and experimental evidence: 18,37 it was suggested that with increasing lateral size of graphene, a higher amount of lowfrequency acoustic phonons is excitable, thus enhancing its intrinsic TC. 17,18 However, the highest TC enhancement and TC efficiency were measured for GNPs with the smaller MLD (H-15 GNP) for both base fluids (Figure 5).…”
Section: Resultsmentioning
confidence: 88%
“…As shown in Figure 2c,d, we can find that the flakes of graphene are large and lateral dimensions are above 10 μm through AFM, which has a great influence on TC and anisotropy. 50 At the same time, we measured the thickness of the graphene to calculate the number of graphene layers and randomly selected 100 graphene flakes for the AFM height profile analysis. The statistical results are shown in Figure 2e, and it can be found that about 92% of the graphene flakes were less than 10 layers.…”
Section: Resultsmentioning
confidence: 99%
“…fabricated composite materials with different graphene loadings based on mineral oil. [ 184 ] The κ value reached 7.1 W m –1 K –1 , which showed superiority over some commercial products. They also investigated the relationship between thermal contact resistance and graphene loading.…”
Section: The Development In 2d Materials For Thermal Dissipation Appl...mentioning
confidence: 96%